Cereal-legume intercropping enhances the quality of feedstock for lignocellulosic bioethanol production by reducing the carbon: nitrogen ratio - Md Raseduzzaman; Gokul Gaudel; Stephen Okoth Aluoch; Arbindra Timilsina (Discover Agriculture)
Abstract Bioethanol production from cereal straw is a sustainable alternative to meet the current energy demand, but its low nitrogen (N) content and high carbon to nitrogen (C/N) ratio are problematic during bioethanol processing. Intercropping cereals with legumes may increase the N content and reduce the C/N ratio in the harvested straw biomass. In order to investigate the combined production of food, feed, and suitable feedstock (low C/N ratio) for lignocellulosic bioethanol production, a field experiment on cereal-legume intercropping was carried out in southern Sweden. In the experiment, autumn-sown cereals (wheat, triticale, and rye) were grown as monocrops with two different N fertilization levels (60 and 120 kg N ha−1) or intercropped with autumn-sown or spring-sown (undersown) clover-grass, autumn-sown or spring-sown (undersown) alfalfa, or autumn-sown faba bean. Total grain dry matter yield, cereal grain protein content, straw dry matter yield, and straw biomass C/N ratio were estimated. The results showed that the intercrops produced more straw biomass and had a lower C/N ratio, but produced less grain, than cereal monocrops. Among the cereals, rye showed significantly higher grain and straw yields, but lower grain protein content, in all treatments. Among the intercrop treatments, cereal with spring-sown clover-grass produced higher grain and straw yields and had a significantly lower C/N ratio (38:1) than the other treatments. Thus, cereal with spring-sown (undersown) clover-grass is a promising cropping system for lignocellulosic bioethanol production.